Arizona Water Information Center: Foundation and Activities - Foster, Kennith E. (Arizona-Nevada Academy of Science, 1985)
From the Proceedings of the 1985 Meetings of the Arizona Section - American Water Resources Association and the Hydrology Section - Arizona-Nevada Academy of Science - April 27, 1985, Las Vegas, Nevada